Pengaruh Model Pembelajara Inkuiri Terbimbing Berbantuan Simulasi PhET Terhadap Keterampilan Proses Sains Peserta Didik SMAN 1 Tanjung Tahun Ajaran 2019/2020 - Veza Aulia; Hairunisyah Sahidu; Gunawan Gunawan (Department of Physics Education, Universitas Mataram, 2019)
This research is aimed to determine the effect of guided-inquiry learning model using PhET simulation on creativity at SMAN 1 Tanjung of academic year 2019/2020. This research is quasi-experimental with non-equivalent control group design. The population of this research is all student of grade XI SMAN 1 Tanjung of academic year 2019/2020, while the sampling technique used purposive sampling, while the sampling are the student of grade XI MIPA 2 as the experimental group and the student of grade XI MIPA 1 as control group. Creativity data be measured on creativity test which the type test used 7 essay. The research hypothesis was tested using t-test independent. The result of t-test show that tobtained>ttable. It means that there is the effect of guided-inquiry learning model using PhET simulation on creativity at SMAN 1 Tanjung of academic year 2019/2020.